The first trigonotarbid arachnid from Ukraine - Dunlop, Jason A.; Dernov, Vitaly S. (Acta Geologica Polonica, 2023)
The extinct arachnid order Trigonotarbida Petrunkevitch, 1949 is reported here for the first time from Ukraine. The material consists of an opisthosoma preserved in ventral view from the upper Carboniferous (lower Moscovian; Paralegoceras–Eowellerites ammonoid zone) of the Gorlivka locality in the Donets Basin, eastern Ukraine. Formal assignment to a family or genus is difficult, but the preserved ventral anatomy is consistent with a member of the families Aphantomartidae Petrunkevitch, 1945, Kreischeriidae Haase, 1890 or Eophrynidae Karsch, 1882. It is noteworthy for expanding the known distribution of trigonotarbids in Europe and is only the second Palaeozoic arachnid to be formally described from Ukraine; the other being the carapace of a whip scorpion (Thelyphonida Latreille, 1804) from Lomovatka in the Luhansk Region, also in the Donets Basin.
Keywords: Carboniferous; Moscovian; Arachnida; Trigonotarbida; Donets Basin; Ukraine